Healthcare-seeking behavior for diarrhea in under-five children and associated factors in sub-Saharan Africa: a multilevel robust Poisson regression model - Tebeje, Tsion Mulat; Tesfaye, Solomon Hailemariam; Abebe, Mesfin; Seboka, Binyam Tariku; Tesfa, Getanew Aschalew; Seifu, Beminate Lemma; Mare, Kusse Urmale; Aragaw, Fantu Mamo (Frontiers in Public Health, 2024)
Background: Diarrhea is one of the leading causes of child death in sub-Saharan Africa (SSA). Children with diarrhea for whom medical advice or treatment is not sought are at high risk of poor health outcomes and increased mortality, requiring prompt and adequate treatment. However, studies that have been conducted on the factors influencing healthcare-seeking behavior (HSB) for diarrhea in under-five children in SSA are scarce. Therefore, the purpose of this research was to determine the variables related to HSB for diarrhea in children under the age of five. Methods: A secondary data analysis was conducted on the most recent data from the Demographic and Health Surveys in 35 SSA countries. The study included a total weighted sample of 51,791 children under the age of five with diarrhea. We presented the adjusted prevalence ratio and the 95% confidence interval in the multivariable multilevel robust Poisson regression analysis to show the statistical significance and strength of the association between HSB and its determinants. Results: The pooled prevalence of HSB for diarrhea in under-five children was 58.71% (95%CI: 55.39 to 62.04). Factors found to be associated with HSB included maternal age, education and working status, antenatal care visits, postnatal checkups for the child, wasting, distance to a health facility, SSA region, and country income level. Conclusion: More than forty percent of under-five children with diarrhea in SSA did not receive medical advice or treatment. To improve healthcare-seeking behavior, effective health policy interventions are necessary. These include enhancing the education and employment status of mothers, promoting regular antenatal and postnatal care visits, building health facilities in close proximity, and raising awareness in the community about the importance of seeking healthcare services for malnourished children.